The teachings of Salafi in life with the Ahmad family comic peirce's semiotic analysis - Mokhammad Khadiid Syaaifullah (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2020)
wt,1/irh,c.1